Printability and freeze–thaw durability of wheat-straw-fibre modified 3D-printed recycled aggregate concrete - Yuxin Zhao; Xinyue Xi; Yuanxun Zheng; Yate Li; Shiao Yan; Zichen Zeng; Qiao Dong (European Journal of Environmental and Civil Engineering, 2026)

A compact isolator for multi-directionally coupled vibration - Mingzhu Jin; Ge Yan; Xiang Yu; Xiuhui Hou; Zichen Deng; Li Cheng (Engineering Structures, 2026)

Evolution and drivers of surface solar radiation over China since the mid-twentieth century - Anna Li; Zichen Li; Hanyu Zhang; Boyang Jiao; Sihao Wei; Martin Wild; Qingxiang Li (Climate Dynamics, 2026)

In situ white-to-brown reprogramming to induce adipocyte thermogenesis by engineered bacteria for breast cancer immunotherapy - Lulu An; Zichen Yang; Rongjie Li; Jianwei Cheng; Yanni Cai; Haiqing Dong; Yiqiong Liu; Yan Li; Yongyong Li (Chemical Engineering Journal, 2026)

Boosting the performance of perovskite quantum dot light-emitting diodes with organic phosphine post-passivation - Zichen Zhang; Xiansheng Li; Xin Luo; Amjad Ali; Yifei Wang; Yuqin Su; Le Ma; Hengyang Xiang; Savas Sonmezoglu; Glib V. Baryshnikov; Albert G. Nasibulin; Bo Xu (Chemical Engineering Journal, 2026)

Microbial-mediated attenuation of carbonaceous organics within urban sewers: Insights from in-pipe sediments microbial communities and metagenomic analyses - Yue Zheng; Xiang Li; Zichen Jia; Yan Qi; Hailong Yin (Bioresource Technology, 2026)

Iron-bearing halloysite for wetland remediation: Curvature-controlled oxidation pathways and ecological implications - Zihan Shu; Zhiyan Feng; Chencheng Qin; Aoqiang Shu; Limei Shi; Miao Li; Zichen Shangguan; Wenyan Zhou; Ying Li; Xingzhong Yuan; Hou Wang (Water Research, 2026)

Optimization and characterization of a low-toxicity trans-anethole nanoemulsion for controlling the soil-borne bacterial pathogen Ralstonia solanacearum - Yao Wang; Yonghao Liu; Lei Yang; Zichen Li; Mengxiao Xie; Deping Ke; Gui Gao; Zhijun Chen; Jiaxi Yuan; Hong Zhou; Shili Li; Wei Ding (Pesticide Biochemistry and Physiology, 2026)

Low-temperature plasma catalysis for VOCs control: Mechanistic insights and hybrid strategies - Junhui Li; Yuan Liu; Zhencheng Xing; Yide Jiang; Zichen Xu; Xuebin Lu; Yifei Sun; Yong Yin (Environmental Research, 2026)

Stabilization mechanisms of blue financial instruments against marine productivity fluctuations in China's coastal regions under climate variability - Ming Li; Xianjun Bao; XueQin Zhong; Zichen Liu (Environmental Development, 2026)

Hierarchical in situ biomineralization-enhanced electroactive biofilm for high-efficiency antibiotic degradation - Zichen Li; Qi Qiu; Yan Feng; Shuming Yang; Yanzhen Yu (Bioresource Technology, 2026)

Corrigendum to “Fluoride-induced male reproductive toxicity: Dual-tissue pyroptosis in the gut-testis axis mediated by inflammatory cytokines”, J. Hazard. Mater. (2026) 142537 - Shu Niu; Yuhui Du; Bin Liu; Zichen Feng; Guoqing Wang; Chunxiang Li; Yan Wang; Qing Sun; Fangfang Yu; Guoyu Zhou; Yue Ba (Journal of Hazardous Materials, 2026)

Fluoride-induced male reproductive toxicity: Dual-tissue pyroptosis in the gut-testis axis mediated by inflammatory cytokines - Shu Niu; Yuhui Du; Bin Liu; Zichen Feng; Guoqing Wang; Chunxiang Li; Yan Wang; Qing Sun; Fangfang Yu; Guoyu Zhou; Yue Ba (Journal of Hazardous Materials, 2026)

Lactiplantibacillus plantarum F190 and its exopolysaccharides modulate the quality of fermented milk by regulating protein structure and gel network formation - Zichen Li; Xueyan Jia; Yanfeng Tuo; Wudeng Wang; Shujuan Jiang (Food Bioscience, 2026)

Molecularly functionalized high-Q THz metasurface via q-BIC for selective HbA1c detection - Chang Liu; Min Gao; Zichen Zhang; Junxiao Liu; Ligeng Jin; Xin Tian; Lijun Jiang; Zhongmei Zheng; Chuanyue Li; Jiaming Feng; Xingyu Liao; Zhihang Long; et al. (Chemical Engineering Journal, 2026)

The interdecadal Pacific oscillation drives an extratropical tripole pattern in northern hemisphere summer rainfall anomalies - Zichen Tang; Song Yang; Noel Keenlyside; Lingling Suo; Hanjie Fan; Qingquan Li; Guillaume Gastineau; Tian Tian (Atmospheric Research, 2026)

Uncertainty quantification in the deployment of tensegrity - Haoran Zou; Alessandro A. Quarta; Lei Wu; Luisa Boni; Wenhao Li; Songlin Bai; Zichen Deng (Advances in Space Research, 2026)

Epigenetic and DNA-repair programs in corpus cavernosum endothelium: genome stability and erectile dysfunction - Zichen Li; Xiaobin Wang (Genome Instability & Disease, 2026)

Regulating the hydrogen transfer pathways for electrochemical nitrate-to-ammonia at industrial current density - Zeyu Li; Zichen Shi; Chu Zhang; Chunshuang Yan; Shijie Chen; Nian Ran; Chenhui Yin; Qingyu Yan; Chade Lv (Science Bulletin, 2026)

Thiosulfate-Driven redox buffering enables efficient nitrogen removal and norfloxacin degradation in mixed denitrifying systems - Jin Qian; Xinqi Li; Xiangning Xu; Dandan Zhang; Guoping Xiang; Zichen Wang; Zhen Zhang; Mengxue Liu; Wen Hao; Di Wu (Bioresource Technology, 2026)

Synergistic inversion of maize leaf chlorophyll using multi-source remote sensing data - Shaoping Sun; Jixuan Yan; Guang Li; Zichen Guo; Wenning Wang; Qiang Li; Kejing Cheng; Xuchun Li; Jiaqin Yuan; Changbo Wu (Irrigation Science, 2026)

Electric-field-driven ultra-fine fibres (EDF): A sustainable and intelligent platform for future food packaging - Jun-Hu Cheng; Kai Zhang; Zichen Li; Da-Wen Sun (Trends in Food Science & Technology, 2026)

Efficient persulfate activation via a novel layered porous biochar enhanced with nano-zero-valent iron loading and synergistic sulfidation modification: Performance and mechanism - Lei Shen; Zichen Qin; Yuanding Shi; Yan Li; Pengyao Guo; Jinwei Zhang; Yijun Shen; Chun Yang; Yuchen Zeng; Dongxiao Sun; Zhiqiang Dong; Lei Ding (Journal of Water Process Engineering, 2026)

Low-dose fluoride and lead co-exposure alters bone mineral density in youth: A nationally representative cross-sectional study - Chunxiang Li; Zeyuan Niu; Yuhui Du; Lihong Yang; Fan Wu; Xinxin Hu; Xiaohang Meng; Zichen Feng; Shu Niu; Qing Sun; Yan Wang; Xiaoli Fu; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Integrated assembly the multifunctional composite films using carbon dots greenly synthesized in situ on cellulose nanofibers for active fruit preservation - Lijuan Lan; Jiazhen Cao; Zichen Li; Jun-Hu Cheng (Food Chemistry, 2026)

Plasma assisted electrospinning technology for functional food packaging: Strategies, applications, and prospects - Kai Zhang; Zichen Li; Jun-Hu Cheng (Food Packaging and Shelf Life, 2026)

Unlocking low-temperature stable cycling of ultrahigh-nickel LiNi0.91Co0.06Mn0.03O2 cathodes by modulating interfacial chemistry through coordination environment - Zichen Liu; Sida Huo; Ben Su; Lei Chai; Guoliang Chen; Chenhang Zhang; Meng Li; Yingjin Wei; Yue Wang; Jingyi Qiu; Wendong Xue (Chemical Engineering Journal, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Advances and Perspectives in Atmospheric Environment Modeling in China - Zifa Wang; Xinwei Li; Meng Gao; Baozhu Ge; Xiao Tang; Xueshun Chen; Qizhong Wu; Lin Wu; Zhe Wang; Ting Yang; Xiaole Pan; Huansheng Chen; et al. (Advances in Atmospheric Sciences, 2026)

Chemo-mechanical surface engineering via in situ boronation enables 50% RH-stable Li5FeO4 prelithiation additives - Chenhang Zhang; Sida Huo; Ben Su; Zichen Liu; Meng Li; Anbin Zhou; Lei Chai; Yue Wang; Jingyi Qiu; Wendong Xue (Chemical Engineering Journal, 2026)

Comparative genomics reveals that Bifidobacterium longum subsp. longum BZG4 alleviates constipation in mice via synergistic xylooligosaccharide - YaXin Gu; Qingqiu Ye; Xin Feng; Junzhu Li; Zichen He; Ming Zhang; Yanling Hao; Zhengyuan Zhai (Food Bioscience, 2026)

A dual conductive network-constructed ionogel sensor for human facial expression and action recognition based on the BDAA/AgNWs composition - Yanfang Guan; Han Wang; Minggang Shen; Zichen Li; Zhaoyang Xia; Tong Jin; Zhenxiang Qi; Xiang Li; Ruimeng Jin; Jian Jin; Zhiyong Duan; Guoyong Ye; et al. (Chemical Engineering Journal, 2026)

Recent changes in antarctic surface air temperature based on the fusion of satellite and in-situ measurements - Siqin Xie; Sihao Wei; Zichen Li; Qingxiang Li (Theoretical and Applied Climatology, 2026)

Green light alone sustains the complete soybean life cycle - Zhen Li; Zichen Guo; Gengxue Wu; Jianqiu Guo; Bingjun Jiang; Yanlei Yue (Journal of Photochemistry and Photobiology B: Biology, 2026)

Efficacy of alpha-lipoic acid in mitigating neuropathic pain: mechanistic insights and therapeutic implications - Daosong Dong; Yanbin Sun; Qingqing Sui; Zichen Zhao; Hong Ma; Kai Li; Xue Yu (Inflammopharmacology, 2026)

Predicting soil cadmium spatial distribution with HDXRF coupling to multi-model machine learning in the karst area - Zichen Gu; Hongyan Liu; Xue Mei; Longhua Wu; Ghulam Rasool; Xuexian Li; Yonglin Chen; Hai Zhang; Chunyan Li; Wei Song (Environmental Monitoring and Assessment, 2026)

Notch1-dependent hippocampal apoptosis is associated with monocrotaline-induced anxiety-like behavior - Lai Baochang; Li Fan; Wang Fei; Yan Xianchun; Wang Zichen; Han Mengzhuan; Zhang Yiman; Kang Mengyang; Liu Bing; Wang Ying; Ma Qiang; Jia Pu; et al. (Toxicology, 2026)

Effects of recombinant carrot antifreeze protein concentrations on frozen dough and bread: Insights into dynamic changes of water and ice crystals - Ying Huang; Shenying Zhang; Haojia Zhu; Caiyun Liu; Zichen Huang; Hanzhang Hao; Yingxue Che; Mei Liu; Ying Liang; Xueling Zheng; Chong Liu; Limin Li (Food Chemistry, 2026)

An efficient multi-objective optimization method for inter-basin water diversion based on the rotation vector method for exploring the convex objective space - Zekun Li; Bin Xu; Ping-an Zhong; Jiaying Tan; Ran Mo; Xinrong Wang; Zichen Ren; Guoqing Wang; Jianyun Zhang; Jiangyuan Li; Scott E. Boyce (Environmental Modelling & Software, 2026)

Multi-target synergistic anti-aging: QG extends Caenorhabditis elegans lifespan through DAF-16/FOXO pathways, mitochondrial homeostasis and metabolic reprogramming - Jiahui Wang; Shuqi Li; Zichen Lei; Yantao Xing; Jieshu Li; Jie Guo; Boshi Duan; Yonggang Liu (Biogerontology, 2026)

Experimental evidence of anthropogenic noise-induced perceived risks for a free-living mammal - Xiaotong Mai; Zichen Li; Yixiao Zhu; Tianming Wang (Animal Behaviour, 2026)

Reducing uncertainty in surface solar radiation projections over the Northern Hemisphere using a hierarchical emergent constraint: Insights from CMIP6 and observation reconstruction - Boyang Jiao; Yucheng Su; Liya Chao; Zichen Li; Qingxiang Li; Martin Wild (Atmospheric Research, 2026)

Green flexible job-shop scheduling considering transportation time and machine multi-rotation speeds - Minghai Yuan; Zhen Zhang; Zichen Li; Yang Ye; Fengque Pei; Wenbin Gu (Swarm and Evolutionary Computation, 2025)

An initial subsystem stiffness-integrated seismic performance optimization approach for super high-rise frame-core tube structures using generalized models - Xiao Lai; Zheng He; Jian Yang; Zichen Li (Soil Dynamics and Earthquake Engineering, 2025)

Enhanced efficiency of bacteria-algae symbiotic biofilm reactors in treating coal chemical wastewater: Mechanisms and microbial dynamics - Jingxin Shi; Yuanyuan Yang; Zichen Zhu; Shengyang Li; Haifeng Zhuang (Journal of Environmental Chemical Engineering, 2025)

A novel Pac-Man structured Cu-Fe bimetallic catalyst for enhanced PAA activation: Unveiling the critical role of sulfur species in tetracycline hydrochloride degradation - Zichen Cao; Yan Zhao; Qingqing Li; Fanyue Meng; Mengzhu Yu; Songshan Cao; Guanghong Sheng; Dongdong Ren; Bing Song (Journal of Environmental Management, 2025)

Recovery of industrial waste heat for district heating: A complementary heating method and stakeholder coordination - Zichen Rao; Jiayu Li; Pei Liu; Hao Zhou; Yuqing Chen; Hao Fang; Borong Lin (Energy and Buildings, 2025)

Effect of two Karst-contaminated soils and Chinese cabbage varieties on heavy metal uptake, soil enzyme activities, microbial communities, and soil fauna diversity - Ghulam Rasool; Hongyan Liu; Jiujun Xiao; Xuexian Li; Chunyan Li; Zichen Gu; Hai Zhang (Environmental Geochemistry and Health, 2025)

Efficient biosorption of molybdenum (VI) using Chlorella pyrenoidosa biomass: Mechanistic insights and sustainable application in water remediation - Zhixin Song; Lingfang Cui; Xunan Li; Zichen Zhang; Chao Zhang; Gangfu Song; Yu Zhao; Wenzhong Tang (Journal of Cleaner Production, 2025)

Spectral feature variations of low-iron olivine under intense pulse-laser irradiations - Zichen Wei; Yan Zhuang; Hao Zhang; Pengfei Zhang; Yang Li; Menghua Zhu; Te Jiang; Ronghua Pang (Icarus, 2025)

Free L- and D-amino acids in PM2.5 in a megacity in central China, from the perspectives of pollution characteristics, atmospheric processes and sources - Nan Jiang; Zichen Wang; Yu Zhang; Kaidi Gong; Zhangpeng Guo; Jiasen Guo; Minzhen Li; Ruiqin Zhang; Hang Yuan; Yufen Zhao (Environmental Pollution, 2025)

High energy electron irradiation promotes the space weathering process on the nearside of the Moon - Zhenyu Xu; Yazhou Yang; Longlong Zhang; Shuai Li; Hongwei Li; Panpan Zhang; Mengyuan Zhang; Haolin Yin; Mengze Tao; Zichen Wei; Hao Zhang; Lianghai Xie; et al. (Earth and Planetary Science Letters, 2025)

Reconstruction of vertical temperature profile based on sea surface variables using convolutional neural network - Mengzhu Li; Chi Zhang; Jun Li; Xin Chen; Zichen Wang; Taihong Li (Acta Oceanologica Sinica, 2025)

Livestock manure-based organic fertilization facilitates the transmission of antibiotic resistance genes across the soil-onion continuum: A significant contribution from root exudates - Zixuan Zhao; Bin Luo; Tao Cao; Tongtong Bai; Yifan Sun; Hengrui Liu; Li Zhang; Jun Xie; Jun Wang; Huakang Li; Zichen Duan; Zixuan Gao; et al. (Soil Biology and Biochemistry, 2025)

Tracing toxic pollutants in coastal urban atmosphere: A case study on the particle-size distribution, sources, and health risks of PCDD/Fs, PCBs, PAHs, and substituted PAHs - Zhangpeng Guo; Shuai Sun; Rong Cao; Nan Jiang; Naibing Liang; Zichen Wang; Jiasen Guo; Minzhen Li; Xing Liu; Ningbo Geng; Jiping Chen (Journal of Hazardous Materials, 2025)

Limosilactobacillus reuteri FN041 alleviates cow's milk β-lactoglobulin–induced food allergy through immune modulation and gut microbiota remodeling - Renqiang Yu; Weijia Li; Zhou Zhou; Yue Yin; Zichen Luo; Ce Qi; Shanyu Jiang; Xiaoqing Chen; Danni Ye; Jin Sun (Food Bioscience, 2025)

Global health impacts of PAHs based on high-resolution modeling by dynamic simulation and relative emission downscaling - Zichen Wu; Xueshun Chen; Yuanlin Wang; Wenyi Yang; Yang Wang; Zhe Wang; Huansheng Chen; Lianfang Wei; Wending Wang; Huiyun Du; Zhuoran Wang; Ying Wei; et al. (Atmospheric Environment, 2025)

Fractal Characterization of Pore Structure and Mechanical Degradation in Carbonate Rocks Under Acid Dissolution - Xin Liu; Chen Wang; Ting Lu; Xiaosong Wen; Zichen Li; Yujun Zuo (Geotechnical and Geological Engineering, 2025)

Damage Evolution Modeling of Karst-Affected Dolomite Under Uniaxial Compression - Cheng Li; Chen Wang; Yujun Zuo; Zichen Li; Chaoyuan Yong; Mingguang Wu (Geotechnical and Geological Engineering, 2025)

Effects of Cardiac Rehabilitation Combined with Enhanced External Counterpulsation on Heart Rate Variability and Autonomic Nervous Function in Chronic Heart Failure - Yiliang Yan; Zichen Han; Bowen Zhou; Kui Li; Jintao Hu; Sigong Yang; Jun Zhang; Xuemin Hu (Cardiovascular Toxicology, 2025)

Sources and temporal trends of chlorinated paraffins in PM2.5 in a megacity in central China - Nan Jiang; Jiasen Guo; Zhangpeng Guo; Zhengqing Lv; Yuan Gao; Faqiang Zhan; Zichen Wang; Minzhen Li; Ruiqin Zhang; Haijun Zhang; Ningbo Geng; Jiping Chen (Environmental Pollution, 2025)

Washing-inspired self-cleaning bionic solar interfacial evaporator for highly efficient broad-spectrum desalination - Zichen Li; Chunyan Huang; Shuxia Wei; Jun-Hu Cheng; Yuanyuan Ge; Zhili Li (Chemical Engineering Journal, 2025)

Integrated carbon footprint accounting for coffee: A new perspective on low-carbon and sustainable living - Zichen Li; Xia Li; Qian Jia; Fengting Li (Bioresource Technology Reports, 2025)

Quality changes in the physiology, behaviour, nutrition, and taste of Urechis unicinctus during waterless live transportation - Teng Teng; Yuchun Lu; Zichen Deng; Shuqi Wang; Yuting Yang; Huihong Li; Chun-E Liu (Food Chemistry, 2025)

Significant insights of CaO2 promoting heavy metal complexes removal during a plasma process - Meiqian Lu; Rong Li; Zichen Wang; Yue Liu; Guodong Zhang; Qiuling Ma; Jian Zhou; He Guo; Tiecheng Wang (Journal of Environmental Management, 2025)

Assessing the growth dynamics of Listeria monocytogenes and microbiota in RTE poultry: A combined BP-ANN and traditional approach - Zichen Deng; Wenqian Li; Yihuan Song; Hongyi Wen; Yongxian Zhang; Yan Du; Yan Wang; Can Huang; Jingyu Chen (International Journal of Food Microbiology, 2025)

Pharmacokinetics of honokiol in Trachinotus ovatus following administration of honokiol monomer and Magnolia officinalis extracts - Weiliang Guo; Danyi Wei; Zichen Zhao; Fengxiao Hu; Dahao Wang; Wei Tang; Yan Wang; Hengwei Deng; Jianlong Li; Dongdong Zhang; Zhihong Zhong; Yongcan Zhou (Aquaculture, 2025)

Systems metabolic engineering and process optimization for efficient l-tyrosine production from high-purity glucose syrup in Escherichia coli - Zhichao Chen; Ling Ma; Weiwei Liu; Changgeng Li; Meng Yuan; Zichen Yu; Lanxiao Li; Xiaoguang Fan; Qingyang Xu (Bioresource Technology, 2025)

Nuclear Inclusion Protein B-Driven In Vitro Replication System for Potato Virus Y - Jiayu Fu; Zichen Li; Minjun Liu; Guowei Geng (Potato Research, 2025)

Forest litter decomposition stimulates heterotrophic nitrogen fixation by driving diazotrophic community interactions - Chang Pan; Shuikuan Bei; Zhe Hua; Mengtian Zhou; Zichen Wang; Ruoxian Fu; Xiaogang Li (Biology and Fertility of Soils, 2025)

An Improved ESO-based Line-of-Sight guidance law for path following of underactuated Autonomous Underwater Helicopter with nonlinear tracking differentiator and anti-saturation controller - Haoda Li; Zichen Liu; Jin Huang; Xinyu An; Ying Chen (Ocean Engineering, 2025)

Geopolymer armor-reinforced composite membranes for efficient oil–water separation and dye degradation - Chunyan Huang; Zichen Li; Yuning Pan; Zhili Li; Yuanyuan Ge (Chemical Engineering Journal, 2025)

The reaction mechanism and application of advanced oxidation of peracetic acid: A review - Zichen Cao; Qingqing Li; Fanyue Meng; Bing Song; Guanghong Sheng (Journal of Environmental Chemical Engineering, 2025)

The mechanism of pore pressure and adsorption swelling effect on permeability during geological storage of carbon dioxide in coal seams - Zhenbao Li; Zichen Fan; Hu Wang; Shaorui Wang; Chao Li (Fuel, 2025)

Bonding interlocked polyaniline with hydrated vanadium oxide for dynamic thermal radiation regulators - Zichen Ren; Dongqi Liu; Leipeng Zhang; Bo Wang; Shanshan Song; Tingting Hao; Yike Zhang; Jiupeng Zhao; Yao Li (Chemical Engineering Journal, 2025)

A coupled hydro-mechanical damage constitutive model for carbonate rocks subjected to karst erosion - Chaoyuan Yong; Chen Wang; Yujun Zuo; Aoli Li; Zichen Li; Shan Jiang; Xinxin Huang (Carbonates and Evaporites, 2025)

Electrochemistry-empowered nano-labeling for versatile aptamer-based biosensing of tumor-associated proteins - Ya Cao; Xiaomeng Yu; Yue Cao; Zichen Huang; Jiancheng Xu; Jing Zhao; Genxi Li (Chemical Engineering Journal, 2025)

Determination and quantitative evaluation of early postharvest hidden damage in fresh strawberry fruit based on coupling of dynamic finite element method and response surface methodology - Jie Guo; Yufei Liu; Manoj Karkee; Xuping Feng; Zichen Huang; Yuwei Wang; Wenkai Zhang; Xiaoli Li; Yong He (Computers and Electronics in Agriculture, 2024)

P-phenylenediamines (PPDs) and 6PPD-quinone in tunnel PM2.5: From the perspective of characterization, emission factors, and health risks - Nan Jiang; Minzhen Li; Zichen Wang; Xuexin Hao; Zhangpeng Guo; Jiasen Guo; Ruiqin Zhang; Haijun Zhang; Jiping Chen; Ningbo Geng (Journal of Hazardous Materials, 2024)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

Efficient catalytic oxidation of xylose to formic acid with the oxygen vacancies of CeO2 promoted the vanadium catalysts anchored on biochar - Shuxia Wei; Tong Sun; Wenbo Liao; Zhili Li; Zichen Li; Yong Sun (Chemical Engineering Journal, 2024)

Nitrogen deposition enhances accumulation of microbial and plant-derived carbon in forest soils: a global meta-analysis - Chenying Wang; Xiaoyan Li; Meng Zhang; Zichen Han; Yun Xia; Pingping Lian; Liuming Yang; Kai Yue; Yuexin Fan (Plant and Soil, 2024)

Establishment of a semi-continuous scale-down clone screening model for intensified perfusion culture - Tao Sun; Yu Zhang; Hengrui Liang; Wenjing Fang; Zichen Qian; Kee Wee Tan; Junjie Li; Xiang Zheng; Mingyue Fang; Hang Zhou; Weichang Zhou; Sam Zhang (Biotechnology Letters, 2024)

Earth observation reveals the shifting patterns of China's lake colour driven by climate change and land cover - Huanchang Ying; Shenglei Wang; Bing Zhang; Zichen Mao; Fangfang Zhang; Junsheng Li (Journal of Environmental Management, 2024)

Response of heterocyst differentiation of Dolichospermum to different forms of nitrogen deficiency - Zichen Liu; Fazhi Xie; Liya Wang; Li Yu; Xiaoli Shi; Zhen Yang; Min Zhang (Harmful Algae, 2024)

Exploration and application of treating OSCC by a precisely concentrated synergistic agent in combination with thermally responsive release of effective therapeutic dosages of cisplatin - Shilin Guo; Tao Liu; Xinyuan Peng; Xinyu Zhang; Yangguang Li; Linzhong Yang; Wenguang Xu; Zheng Wei; Diya Xie; Lin Chen; Zichen Cao; Xiteng Yin; et al. (Chemical Engineering Journal, 2024)

Rapid-response electrochromic devices with self-wrinkling polyaniline for enhanced infrared emissivity modulation - Yike Zhang; Dongqi Liu; Zichen Ren; Wenchao Liu; Bo Wang; Shanshan Song; Tingting Hao; Lei Xu; Haoyu Ji; Jiawu Sun; Leipeng Zhang; Yao Li (Chemical Engineering Journal, 2024)

High-level and -yield orotic acid production in Escherichia coli through systematic modular engineering and “Chaos to Order Cycles” fermentation - Changgeng Li; Tangen Shi; Wenjing Fan; Meng Yuan; Lanxiao Li; Zichen Yu; Zhichao Chen; Qingyang Xu (Bioresource Technology, 2024)

Effects of socioeconomic status and regional inequality on the association between PM2.5 and its components and cardiometabolic multimorbidity: A multicenter population-based survey in eastern China - Zhiqian Cui; Xinxu Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Rong Song; Jintao Liu; Rubing Pan; Weizhuo Yi; Xiaoyu Jin; Jian Song; et al. (Science of The Total Environment, 2024)

Modification of glycosyltransferase SrUGT76G1 based on computer-aided screening of mutation sites for efficient synthesis of rebaudioside M - Liang Zhao; Yaqi Liu; Yingnan Li; Fei Pan; Ting Yang; Zichen Yang; Xiang Lv; Lei Zhao; Chengtao Wang (Food Bioscience, 2024)

Capsaicin reduces blood glucose and prevents prostate growth by regulating androgen, RAGE/IGF-1/Akt, TGF-β/Smad signalling pathway and reversing epithelial-mesenchymal transition in streptozotocin-induced diabetic mice - Hui Sun; ZiTong Wang; BingHua Tu; ZiChen Shao; YiDan Li; Di Han; YinJie Jiang; Peng Zhang; WeiChang Zhang; YunYan Wu; XiaoMing Wu; Chi-Ming Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Contrast in Secondary Organic Aerosols between the Present Day and the Preindustrial Period: The Importance of Nontraditional Sources and the Changed Atmospheric Oxidation Capability - Yingchuan Yang; Wenyi Yang; Xueshun Chen; Jiawen Zhu; Huansheng Chen; Yuanlin Wang; Wending Wang; Lianfang Wei; Ying Wei; Qian Ye; Huiyun Du; Zichen Wu; et al. (Advances in Atmospheric Sciences, 2024)

Simulating liquefaction-induced resuspension flux in a sediment transport model - Zichen Zhu; Xing Du; Bingchen Liang; Linfeng Wang; Yupeng Song; Ping Li; Yaoshen Fan; Shuhua Bian; Yongzhi Wang; Yongqiang Zhang; Bing Li (Water Research, 2024)

Characteristics analysis of leakage diseases of Beijing underground subway stations based on the field investigation and data statistics - Hua Peng; Yujie Li; Xiaokai Niu; Haidong Tang; Xue Meng; Zichen Li; Kuangdi Wan; Wei Li; Wei Song (Transportation Geotechnics, 2024)

p‑Phenylenediamine antioxidants in PM2.5: New markers for traffic in positive matrix factorization source apportionment - Nan Jiang; Xuexin Hao; Zichen Wang; Minzhen Li; Dong Zhang; Rong Cao; Ruiqin Zhang; Haijun Zhang; Jiping Chen; Ningbo Geng (Journal of Hazardous Materials, 2024)

Ni/Ni4N nanoparticles anchored on 3D necklace-like carbon framework as free-standing bifunctional host for practical Li-S full cells - Zichen Guo; Yinuo Li; Yuan Tian; Cheng Wang (Chemical Engineering Journal, 2024)

Injectable photocrosslinkable acellular cartilage matrix hydrogel loaded with exosomes for promoting growth plate injury repair - Xinxin Si; Quan Zhang; Bo Ning; Lei Qiang; Qiang Li; Yihao Liu; Minjie Fan; Jing Shan; Guanlu Shen; Zichen Lin; Pengfei Zheng (Chemical Engineering Journal, 2024)

Correlations between bone metabolism biomarkers and fluoride exposure in adults and children - Shuo Yang; Shuiyuan Yu; Yuhui Du; Zichen Feng; Xuecheng Jiao; Qinyang Li; Jingjing Wu; Lei Sun; Juan Zuo; Xiaoli Fu; Zhiyuan Li; Hui Huang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

A facile and on-demand optimizing strategy for polyurethane elastomers via programmable hydrogen bonding - Zichen Bai; Xiaodong Li; Tianhao Wu; Hao Jiang; Xudong Zhang; Lichen Zhang; Yi Yang; Shuang Liu; Lisha Lei; Ningning Song; Zhengdi Wang; Xing Su; et al. (Chemical Engineering Journal, 2024)

Experimental Study on the Directional Effect of Damage in Marble Under Different Impact Modes - Dongyang Wu; Liyuan Yu; Haijian Su; Wei Li; Shentao Geng; Zichen Yuan (Rock Mechanics and Rock Engineering, 2024)

Novel Coumarins Derivatives for A. baumannii Lung Infection Developed by High-Throughput Screening and Reinforcement Learning - Jing Li; Zhou Lu; Liuchang Wang; Huiqing Shi; Bixin Chu; Yingwei Qu; Zichen Ye; Di Qu (Journal of Neuroimmune Pharmacology, 2024)
With the increasing resistance of Acinetobacter baumannii ( A. baumannii ) to antibiotics, researchers have turned their attention to the development of new antimicrobial agents. Among them, coumarin-based heterocycles have attracted much attention due to their unique biological activities, especially in the field of antibacterial infection. In this study, a series of coumarin derivatives were synthesized and screened for their bactericidal activities (Ren et al. 2018; Salehian et al. 2021). The inhibitory activities of these compounds on bacterial strains were evaluated, and the related mechanism of the new compounds was explored. Firstly, the MIC values and bacterial growth curves were measured after compound treatment to evaluate the antibacterial activity in vitro. Then, the in vivo antibacterial activities of the new compounds were assessed on A. baumannii -infected mice by determining the mice survival rates, counting bacterial CFU numbers, measuring inflammatory cytokine levels, and histopathology analysis. In addition, the ROS levels in the bacterial cells were measured with DCFH-DA detection kit. Furthermore, the potential target and detailed mechanism of the new compounds during infection disease therapy were predicted and evidenced with molecular docking. After that, ADMET characteristic prediction was completed, and novel, synthesizable, drug-effective molecules were optimized with reinforcement learning study based on the probed compound as a training template. The interaction between the selected structures and target proteins was further evidenced with molecular docking. This series of innovative studies provides important theoretical and experimental data for the development of new anti- A. baumannii infection drugs.

Simulation and experiment of air-duct heating equipment using electricity in a sheep barn using computational fluid dynamics - Zichen Liu; Honglei Cen; Min Lu; Jingbin Li; Qiang Cai; Jing Nie; Baoqin Wen; Yalei Xu (Computers and Electronics in Agriculture, 2024)

Spatio-temporal variation and drivers of blue carbon sequestration in Hainan Island, China - Zichen Li; Ling Liu; Chuhan Sun; Xiaoyang Shan; Hongwei Zhao (Marine Environmental Research, 2024)

Nano-scale and micron-scale plastics amplify the bioaccumulation of benzophenone-3 and ciprofloxacin, as well as their co-exposure effect on disturbing the antioxidant defense system in mussels, Perna viridis - Junnan Li; Luhua You; Zichen Xu; Karina Yew-Hoong Gin; Yiliang He (Environmental Pollution, 2024)

Chitosan-derived carbon aerogel modified with lignin carbon quantum dots for efficient solar evaporation - Zichen Li; Dazhen Li; Shuxia Wei; Xin Jin; Zheng Zhang; Lin Liu; Yuanyuan Ge; Zhili Li (Chemical Engineering Journal, 2024)

Carbon quantum dots assisted BiFeO3@BiOBr S-scheme heterojunction enhanced peroxymonosulfate activation for the photocatalytic degradation of imidacloprid under visible light: Performance, mechanism and biotoxicity - Sai Bai; Ting Lv; Miaomiao Chen; Chang Li; Zichen Wang; Xinyao Yang; Tianjiao Xia (Science of The Total Environment, 2024)

Green space and its types can attenuate the associations of PM2.5 and its components with prediabetes and diabetes—— a multicenter cross-sectional study from eastern China - Zhiqian Cui; Rubing Pan; Jintao Liu; Weizhuo Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Li Liu; Ning Wei; Rong Song; Jiajun Yuan; et al. (Environmental Research, 2024)

Development of a Three-dimensional Stress Monitoring System for Coal Rock and its Application in a Mine - Rongxi Shen; Zhenhai Hou; Zichen Yuan; Yuewen Li; Yu Gu (Rock Mechanics and Rock Engineering, 2024)

Source and health risk of urinary neonicotinoids in Tibetan pregnant women - Yuanping Wang; Yangzong Gesang; Yi Wang; Zichen Yang; Ke Zhao; Jiaqi Liu; Chunxia Li; Luobu Ouzhu; Hexing Wang; Yue Chen; Qingwu Jiang (Chemosphere, 2024)

Bio-inspired thermal actuator for dynamic multispectral modulation from visible to microwave wavelengths - Shanshan Song; Gaoping Xu; Tingting Hao; Zichen Ren; Dongqi Liu; Yike Zhang; Jiupeng Zhao; Leipeng Zhang; Yao Li (Chemical Engineering Journal, 2024)

Record-breaking High-temperature Outlook for 2023: An Assessment Based on the China Global Merged Temperature (CMST) Dataset - Zichen Li; Qingxiang Li; Tianyi Chen (Advances in Atmospheric Sciences, 2024)

Dust phase and window film phase phthalates in dormitories: profile characteristics, source screening, and estimated gas-phase concentration and dermal exposure comparison - Zichen Guo; Lixin Wang; Yatai Li; Zaixing Wu; Kexin Wang; Jiahui Duan (Environmental Science and Pollution Research, 2024)

Fe and Zn co-doped carbon nanoparticles as peroxymonosulfate activator for efficient 2,4-dichorophenol degradation - Xiaojie Qiu; Yingxin Zhao; Zichen Jia; Chenxi Li; Ruotong Jin; Emmanuel Mutabazi (Environmental Research, 2024)

Dynamic layer-by-layer surface self-assembly on aluminum fuel for improving the comprehensive performance of propellants - Lichen Zhang; Zichen Bai; Ruibin Wang; Xiaodong Li; Xing Su; Meishuai Zou (Chemical Engineering Journal, 2024)

A mutation in CsDWF7 gene encoding a delta7 sterol C-5(6) desaturase leads to the phenotype of super compact in cucumber (Cucumis sativus L.) - Haiqiang Zhang; Zichen Liu; Yunxiao Wang; Siyu Mu; Hongzhong Yue; Yanjie Luo; Zhengao Zhang; Yuhong Li; Peng Chen (Theoretical and Applied Genetics, 2024)

Smartphone-Aided Fluorescence Detection of Cardiac Biomarker Myoglobin by a Ratiometric Fluorescent AuNCs-QDs Nanohybrids Probe with High Sensitivity - Zichen Xu; Hedan Xu; Hongliang Duan; Junjie Li; Xiao Hu; Kaixin Jiang; Guixue Wang; Yuanyuan Zhang (Journal of Fluorescence, 2024)

O2 plasma-modified carbon nanotube for sulfamethoxazole degradation via peroxymonosulfate activation: Synergism of radical and non-radical pathways boosting water decontamination and detoxification - Shiqi Liu; Zichen Zhang; Rui Lu; Yuankun Mao; Huiru Ge; Can Liu; Chenxi Tian; Siyuan Yin; Li Feng; Yongze Liu; Chao Chen; Liqiu Zhang (Chemosphere, 2023)

Cheap and easily separate Cs(I) and Rb(I) from high salty solution by forming RbCs–MgHCF - Kang Li; Junjie Xie; Zhuonan Shi; Changli Min; Zichen Yin; Ruixin Ma; Shina Li (Journal of Cleaner Production, 2023)

Enhancing infrared electrochromic properties of the poly(styrene sulfonate) doped polyaniline composite film by morphology regulation - Leipeng Zhang; Tingting Hao; Shanshan Song; Bo Wang; Dongqi Liu; Zichen Ren; Wenchao Liu; Yike Zhang; Gaoping Xu; Xiangqiao Yan; Yuan Lu; Yao Li (Chemical Engineering Journal, 2023)

From Geoparks to Regional Sustainable Development: Geoheritage Protection and Geotourism Promotion of Geoparks in Hebei Province, China - Yanjie Wang; Xiuming Li; Zichen Han; Jinfang Han; Xiaoxiao Pang; Wenli Song; Qinpeng Wang (Geoheritage, 2023)

Oridonin attenuates the progression of atherosclerosis by inhibiting NLRP3 and activating Nrf2 in apolipoprotein E-deficient mice - Lei Wang; Xiaoqi Zhao; Jiawen Ding; Yutong Liu; Han Liu; Lei Zheng; Hongting Zhao; Zichen Sun; Kuanyu Li; Jing Cai; Tong Qiao (Inflammopharmacology, 2023)
Oridonin, a well-known traditional Chinese herbal medicinal product isolated from Isodon rubescens (Hemsl.) H.Hara, has many potential properties, including anti-inflammatory and antioxidant activities. However, there is no evidence whether oridonin have a protective effect on atherosclerosis. This study focused on the effects of oridonin on oxidative stress and inflammation generated from atherosclerosis. The therapeutic effect on atherosclerosis was evaluated by intraperitoneal injection of oridonin in a high-fat fed ApoE −/− mouse model. We isolated mouse peritoneal macrophages and detected the effect of oridonin on oxidized low-density lipoprotein-induced lipid deposition. Oil red O staining, Masson's staining, dihydroethidium fluorescence staining, immunohistochemical staining, western blotting analysis, immunofluorescence, enzyme-linked immunosorbent assay and quantitative real-time PCR were used to evaluate the effect on atherosclerosis and explore the mechanisms. Oridonin treatment significantly alleviated the progression of atherosclerosis, reduced macrophage infiltration and stabilized plaques. Oridonin could significantly inhibit inflammation associated with NLRP3 activation. Oridonin significantly reduced oxidative stress by blocking Nrf2 ubiquitination and degradation. We also found that oridonin could prevent the formation of foam cells by increasing lipid efflux protein and reducing lipid uptake protein in macrophages. Oridonin has a protective effect on atherosclerosis in ApoE −/− mice, which may be related to the inhibition of NLRP3 and the stabilization of Nrf2. Therefore, oridonin may be a potential therapeutic agent for atherosclerosis.

Assessment of Atmospheric Reanalysis Data Based on Buoy Observations over the Tropical Western Indian Ocean in 2019 - Yulan Luo; Lin Liu; Oloo Paul; Sagero Philip; Kuiping Li; Yang Yang; Qinglei Su; Qiuchi Li; Zichen Miao (Journal of Ocean University of China, 2023)

Tris(1,3-dichloro-2-propyl) Phosphate Inhibits Early Embryonic Development by Binding to Gsk-3β Protein in Zebrafish - Zichen Yu; Yongkang Zhang; Ren Kong; Yongjie Xiao; Boqun Li; Chunsheng Liu; Liqin Yu (Aquatic Toxicology, 2023)

Correction: Regulation of PPARγ/CPT-1 expression ameliorates cochlear hair cell injury by regulating cellular lipid metabolism and oxidative stress - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Ting Zhang; Baiya Li; Xiaoyan Ma; Qun Wu; Xudong Ma (Molecular Genetics and Genomics, 2023)

Regulation of Hippo/YAP signaling pathway ameliorates cochlear hair cell injury by regulating ferroptosis - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Xiaoyan Ma; Ting Zhang; Baiya Li; Xudong Ma (Tissue and Cell, 2023)

Giant nonlocal edge conduction in the axion insulator state of MnBi2Te4 - Yaoxin Li; Chang Liu; Yongchao Wang; Zichen Lian; Shuai Li; Hao Li; Yang Wu; Hai-Zhou Lu; Jinsong Zhang; Yayu Wang (Science Bulletin, 2023)

Exposure of Tibetan pregnant women to antibiotics in China: A biomonitoring-based study - Yuanping Wang; Yue Chen; Yangzong Gesang; Zichen Yang; Yi Wang; Ke Zhao; Minghui Han; Chunxia Li; Luobu Ouzhu; Jiwei Wang; Hexing Wang; Qingwu Jiang (Environmental Pollution, 2023)

Disease resistance conferred by components of essential chrysanthemum oil and the epigenetic regulation of OsTPS1 - Chuansong Zhan; Long Lei; Hao Guo; Shen Zhou; Congping Xu; Zixin Liu; Zichen Wu; Yuan Deng; Yuanyuan Miao; Yu Han; Meng Zhang; Hua Li; et al. (Science China Life Sciences, 2023)

Identification of DNA methylation and genetic alteration simultaneously from a single blood biopsy - Xiaomin Chen; Jiahui Liu; Jun Li; Yinpeng Xie; Zichen Yu; Lu Shen; Qingfeng Liu; Wei Wu; Qiang Zhao; Haoxiang Lin; Gaotong Liu; Qiuping Luo; et al. (Genes & Genomics, 2023)

Enhanced cyanogen chloride formation after UV/PS and UV/H2O2 pre-oxidation and chlorination in natural river water - Jie Xu; Yang Guo; Qian Yang; Xueling Bai; Runhua Lu; Menghui Liu; Zichen Kuang; Luo Zhang; Jing Li (Journal of Environmental Sciences, 2023)

A 5.5-kb LTR-retrotransposon insertion inside phytochrome B gene (CsPHYB) results in long hypocotyl and early flowering in cucumber (Cucumis sativus L.) - Liangliang Hu; Miaomiao Zhang; Jingjing Shang; Zichen Liu; Yiqun Weng; Hongzhong Yue; Yuhong Li; Peng Chen (Theoretical and Applied Genetics, 2023)

Regulation of PPARγ/CPT-1 expression ameliorates cochlear hair cell injury by regulating cellular lipid metabolism and oxidative stress - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Ting Zhang; Baiya Li; Xiaoyan Ma; Qun Wu; Xudong Ma (Molecular Genetics and Genomics, 2023)

Biomass-based materials for solar-powered seawater evaporation - Zichen Li; Shuxia Wei; Yuanyuan Ge; Zheng Zhang; Zhili Li (Science of The Total Environment, 2023)

Detection of melamine by using carboxyl-functionalized Ag-COF as a novel SERS substrate - Zichen Yang; Chaoqun Ma; Jiao Gu; Yamin Wu; Chun Zhu; Lei Li; Hui Gao; Wenzhi Yin; Zirui Wang; Guoqing Chen (Food Chemistry, 2023)

High efficiently degradation of organic pollutants via low-speed water flow activation of Cu2O@MoS2/PVDF modified pipeline with piezocatalysis performance - Jingxue Wang; Yanting Liang; Zichen Wang; Bingjie Huo; Chao Liu; Xiaxia Chen; Hongwei Xu; Dongmei Li; Zhaoyou Zhu; Yinglong Wang; Fanqing Meng (Chemical Engineering Journal, 2023)

Efficient electrochemical CO2 reduction to CO by metal and nitrogen co-doped carbon catalysts derived from pharmaceutical wastes adsorbed on commercial carbon nanotubes - Yang Gang; Boyang Li; Siyuan Fang; John Pellessier; Lingzhe Fang; Fuping Pan; Zichen Du; Yun Hang Hu; Tao Li; Guofeng Wang; Ying Li (Chemical Engineering Journal, 2023)

Regulation of defects and nitrogen species on carbon nanotube by plasma-etching for peroxymonosulfate activation: Inducing non-radical/radical oxidation of organic contaminants - Shiqi Liu; Siyuan Yin; Zichen Zhang; Li Feng; Yongze Liu; Liqiu Zhang (Journal of Hazardous Materials, 2023)

Rapid concurrent photocatalysis-persulfate activation for ciprofloxacin degradation by Bi2S3 quantum dots-decorated MIL-53(Fe) composites - Yixin Cao; Xingzhong Yuan; Haoyun Chen; Hou Wang; Yi Chen; Junying Chen; Haoming Huang; Yi Mou; Zichen Shangguan; Xiang Li (Chemical Engineering Journal, 2023)

Study of regional air pollutant dispersion scenarios and atmospheric capacity changes based on spatial structure analysis of source intensity—the case of Hohhot, China - Tianxin Li; Zichen Li; Anni Zou; Shikun Cheng; Xiugui Wang; Nametso Matomela (Air Quality, Atmosphere & Health, 2023)

Electromagnetic radiation prediction of damage characteristics of water-bearing sandstone under cyclic loading and unloading - Rongxi Shen; Hailiang Chen; Enlai Zhao; Taixun Li; Weijun Fan; Zichen Yuan (Bulletin of Engineering Geology and the Environment, 2022)

Piezo1 mediates endothelial atherogenic inflammatory responses via regulation of YAP/TAZ activation - Ying Yang; Danyang Wang; Chunxiao Zhang; Wenqing Yang; Chao Li; Zichen Gao; Ke Pei; Yunlun Li (Human Cell, 2022)

Deep Learning Convolutional Neural Network Applying for the Arctic Acoustic Tomography Current Inversion Accuracy Improvement - Kangkang Jin; Jian Xu; Zichen Wang; Can Lu; Long Fan; Zhongzheng Li; Jiaxin Zhou (Journal of Marine Science and Engineering, 2021)
Warm current has a strong impact on the melting of sea ice, so clarifying the current features plays a very important role in the Arctic sea ice coverage forecasting study field. Currently, Arctic acoustic tomography is the only feasible method for the large-range current measurement under the Arctic sea ice. Furthermore, affected by the high latitudes Coriolis force, small-scale variability greatly affects the accuracy of Arctic acoustic tomography. However, small-scale variability could not be measured by empirical parameters and resolved by Regularized Least Squares (RLS) in the inverse problem of Arctic acoustic tomography. In this paper, the convolutional neural network (CNN) is proposed to enhance the prediction accuracy in the Arctic, and especially, Gaussian noise is added to reflect the disturbance of the Arctic environment. First, we use the finite element method to build the background ocean model. Then, the deep learning CNN method constructs the non-linear mapping relationship between the acoustic data and the corresponding flow velocity. Finally, the simulation result shows that the deep learning convolutional neural network method being applied to Arctic acoustic tomography could achieve 45.87% accurate improvement than the common RLS method in the current inversion.

Mitigation of Cd accumulation in rice with water management and calcium-magnesium phosphate fertilizer in field environment - Wenxuan Luo; Shaona Yang; Mohammad Aman Khan; Jiawei Ma; Weijie Xu; Yaqian Li; Zichen Xiang; Gaoqi Jin; Junwei Jia; Bin Zhong; Lili Duan; Youwei Zhu; et al. (Environmental Geochemistry and Health, 2020)

Effects of adsorption characteristics of different amendments on heavy metals (Pb, Zn, and Cd) - Yaqian Li; Jiawei Ma; Mohammad Shafi; Yefang Sun; Yongqing Li; Zhenhua Chen; Zichen Xiang; Gaoqi Jin; Bin Zhong; Zhengqian Ye; Dan Liu (Journal of Soils and Sediments, 2020)

Genome-wide identification and expression analysis of the CLC superfamily genes in tea plants (Camellia sinensis) - Anqi Xing; Yuanchun Ma; Zichen Wu; Shouhua Nong; Jiaojiao Zhu; Hua Sun; Jing Tao; Bo Wen; Xujun Zhu; Wanping Fang; Xiaocheng Li; Yuhua Wang (Functional & Integrative Genomics, 2020)

MOTS-c peptide regulates adipose homeostasis to prevent ovariectomy-induced metabolic dysfunction - Huanyu Lu; Ming Wei; Yue Zhai; Qingyang Li; Zichen Ye; Li Wang; Wenjing Luo; Jingyuan Chen; Zifan Lu (Journal of Molecular Medicine, 2019)

The complete genome sequence of Escherichia phage SRT7, a novel T7-like phage - Kaili Zhao; Shukai Song; Zhipeng Zhao; Zichen Liu; Yan Ji; Pengfei Gu; Xiangyu Fan; Qiang Li (Archives of Virology, 2019)

Geological significance of the former Xiong’er Volcanic Belt on the southwestern margin of the North China Craton - Guanxu Chen; Jinhai Luo; Huan Xu; Jia You; Yifei Li; Zichen Che (Frontiers of Earth Science, 2019)

Evaluation of the sedative and hypnotic effects of astragalin isolated from Eucommia ulmoides leaves in mice - Xin Li; Zichen Tang; Dongqing Fei; Yunhong Liu; Min Zhang; Shaoyang Liu (Natural Product Research, 2017)

P2Y6 Receptor-Mediated Microglial Phagocytosis in Radiation-Induced Brain Injury - Yongteng Xu; Weihan Hu; Yimin Liu; Pengfei Xu; Zichen Li; Rong Wu; Xiaolei Shi; Yamei Tang (Molecular Neurobiology, 2016)

Tip60 regulates MT1-MMP transcription and invasion of glioblastoma cells through NF-κB pathway - Takahisa Takino; Mitsutoshi Nakada; Zichen Li; Taisuke Yoshimoto; Takahiro Domoto; Hiroshi Sato (Clinical & Experimental Metastasis, 2016)

Epigenetic Signature of Chronic Cerebral Hypoperfusion and Beneficial Effects of S-adenosylmethionine in Rats - Xiangmei Wu; Jing Sun; Xiaowen Zhang; Xiaona Li; Zichen Liu; Qinglin Yang; Liang Li (Molecular Neurobiology, 2014)

Anti-MS4a4B treatment abrogates MS4a4B-mediated protection in T cells and ameliorates experimental autoimmune encephalomyelitis - Yaping Yan; Zichen Li; Guang-Xian Zhang; Mark S. Williams; Gregory B. Carey; Jianke Zhang; Abdolmohamad Rostami; Hui Xu (Apoptosis, 2013)